Y-Chromosomal Variation in Sub-Saharan Africa: Insights Into the History of Niger-Congo Groups - (:unkn) unknown (My University, 2011)
Technological and cultural innovations as well as climate changes are thought to have influenced the diffusion of major language phyla in sub-Saharan Africa. The most widespread and the richest in diversity is the Niger-Congo phylum, thought to have originated in West Africa ∼ 10,000 years ago (ya). The expansion of Bantu languages (a family within the Niger-Congo phylum) ∼ 5,000 ya represents a major event in the past demography of the continent. Many previous studies on Y chromosomal variation in Africa associated the Bantu expansion with haplogroup E1b1a (and sometimes its sublineage E1b1a7). However, the distribution of these two lineages extends far beyond the area occupied nowadays by Bantu-speaking people, raising questions on the actual genetic structure behind this expansion. To address these issues, we directly genotyped 31 biallelic markers and 12 microsatellites on the Y chromosome in 1,195 individuals of African ancestry focusing on areas that were previously poorly characterized (Botswana, Burkina Faso, Democratic Republic of Congo, and Zambia). With the inclusion of published data, we analyzed 2,736 individuals from 26 groups representing all linguistic phyla and covering a large portion of sub-Saharan Africa. Within the Niger-Congo phylum, we ascertain for the first time differences in haplogroup composition between Bantu and non-Bantu groups via two markers (U174 and U175) on the background of haplogroup E1b1a (and E1b1a7), which were directly genotyped in our samples and for which genotypes were inferred from published data using linear discriminant analysis on short tandem repeat (STR) haplotypes. No reduction in STR diversity levels was found across the Bantu groups, suggesting the absence of serial founder effects. In addition, the homogeneity of haplogroup composition and pattern of haplotype sharing between Western and Eastern Bantu groups suggests that their expansion throughout sub-Saharan Africa reflects a rapid spread fol
Keywords: African Research